Control of gene expression by CpG island methylation in normal cells. (26th October 2004) - Strathdee, G.; Sim, A.; Brown, R.
Abstract : The role of DNA methylation in the control of mammalian gene expression has been the subject of intensive research in recent years, partly due to the critical role of CpG island methylation in the inactivation of tumour suppressor genes during the development of cancer. However, this research has also helped elucidate the role that DNA methylation plays in normal cells. At present, it is also clear that DNA methylation forms an important part of the normal cell-regulatory processes that govern gene transcription. Methylation, targeted at CpG islands, is an important part of the mechanisms that govern X-chromosome inactivation; it is also essential for the maintenance of imprinted genes and, at least in some cases, is critical in determining the cell-type-specific expression patterns of genes. Study of these examples will be important in identifying the mechanisms that control targeting of DNA methylation and how these processes are disrupted during disease pathogenesis.